THE DEVELOPMENT AND SIGNIFICANCE OF MINIMALLY INVASIVE SURGERY: METHODS, RESULTS, AND PROSPECTS - Dr. Tanmay Singh Mehta, Dr. Osama (Research Focus International Scientific Journal, 2024)
By lowering hospital stays, recovery times, and patient trauma while preserving or improving procedural efficacy, minimally invasive surgery, or MIS, has revolutionized the field of surgery. The history, evolution, fundamental methods, advantages, drawbacks, and potential future directions of MIS are all examined in this thesis. The research evaluates the effects of robotic surgery, single-incision techniques, and cutting-edge imaging technologies while looking at a variety of applications in disciplines including general surgery, gynecology, orthopaedics, proctology, and cardiology. An examination of current developments and the possibilities for artificial intelligence to further advance MIS is included in the thesis’ conclusion.